2017
DOI: 10.31234/osf.io/nx9rj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political differences in free will belief are driven by differences in moralization

Abstract: Five studies tested whether political conservatives' stronger free will beliefs are driven by their broader view of morality, and thus a broader motivation to assign responsibility. On an individual difference level, Study 1 found that political conservatives' higher moral wrongness judgments accounted for their higher belief in free will. In Study 2, conservatives ascribed more free will for negative events than liberals, while no differences emerged for positive events. For actions ideologically equivalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Regarding responsibility-related judgments for morally relevant behavior, myriad studies have demonstrated that people attribute more responsibility to bad actions and actions with bad outcomes than to closely matched 1) good actions and actions with good outcomes (e.g., Alicke, 1992;Knobe, 2003;Reeder & Spores, 1983), 2) neutral actions and actions with neutral outcomes (e.g., Cushman, Knobe, & Sinnott-Armstrong, 2008;Knobe & Fraser, 2008), and 3) less bad actions and actions with less bad outcomes (e.g., Walster, 1966). Most relevant to the present work, people attribute more free will to morally bad actions and outcomes than to morally good (e.g., Everett et al, 2017) and morally neutral ones (Clark et al, 2014). This body of work seems to suggest that people do not attribute responsibility to morally good actions, but very little work has compared responsibility judgments for morally positive actions to morally neutral ones.…”
Section: The Good the Bad And The Neutralmentioning
confidence: 82%
See 1 more Smart Citation
“…Regarding responsibility-related judgments for morally relevant behavior, myriad studies have demonstrated that people attribute more responsibility to bad actions and actions with bad outcomes than to closely matched 1) good actions and actions with good outcomes (e.g., Alicke, 1992;Knobe, 2003;Reeder & Spores, 1983), 2) neutral actions and actions with neutral outcomes (e.g., Cushman, Knobe, & Sinnott-Armstrong, 2008;Knobe & Fraser, 2008), and 3) less bad actions and actions with less bad outcomes (e.g., Walster, 1966). Most relevant to the present work, people attribute more free will to morally bad actions and outcomes than to morally good (e.g., Everett et al, 2017) and morally neutral ones (Clark et al, 2014). This body of work seems to suggest that people do not attribute responsibility to morally good actions, but very little work has compared responsibility judgments for morally positive actions to morally neutral ones.…”
Section: The Good the Bad And The Neutralmentioning
confidence: 82%
“…Furthermore, people bolster their own belief in free will so as to justify holding others morally responsible (Clark et al, 2014;. Another analysis suggests that there may be individual differences such that people who are particularly inclined to see a variety of negative actions and outcomes (e.g., homelessness, drug addiction) as having moral significance are also more inclined to believe that people have freedom and control over those actions and outcomes (Everett et al, 2017). Relatedly, people tend to downplay their own free will when considering the morally negative consequences of their own behavior (Vonasch, Clark, Lau, Vohs, & Baumeister, 2017).…”
Section: The Function Of Free Will Beliefsmentioning
confidence: 99%
“…Most problematic for compatibilism research, people attribute more free will to performers of morally bad actions than morally good actions and morally neutral actions (Clark et al, 2018; Everett et al, 2018; Feldman et al, 2016), and pondering morally bad actions leads people to increase their belief in the free will of all humankind (Clark et al, 2014). Thus, not only are people motivated to maintain the possibility of free will because they generally believe in free will, but they are particularly likely to assert free will when their judgment has moral significance, as compatibilism judgments do.…”
Section: Introductionmentioning
confidence: 99%